The surge of HBsAb level in a HBsAg-negative ES-SCLC patient after anlotinib plus atezolizumab treatment: A case report - Chen, Gangjun; Tian, Tian; Cai, Xingdong (Frontiers in Oncology, 2023)
Small-cell lung cancer (SCLC) is a poorly differentiated neuroendocrine tumor with endocrine function. For decades, chemotherapy and immune checkpoint inhibitors (ICIs) have been the first-line treatment options. Because of its ability to normalize tumor vessels, anlotinib is recommended as a novel therapy and a third-line treatment. A combination of anti-angiogenic drugs and ICIs can effectively and safely benefit advanced cancer patients. However, immune-related side effects caused by ICIs are common. Hepatitis B virus (HBV) reactivation and hepatitis are common during immunotherapy in patients with chronic HBV infection. A 62-year-old man with ES-SCLC who had brain metastasis was described in this case. It is unusual for a HBsAg-negative patient to develop an increase in HBsAb after receiving atezolizumab immunotherapy. Although some researchers have reported the functional cure of HBV by PD-L1 antibodies, this is the first case that showed a sustained increase in HBsAb levels after anti-PD-L1 therapy. It is related to CD4+ and CD8+ T cell activation and the HBV infection microenvironment. Importantly, this could provide a solution to insufficient protective antibody production after vaccination as well as a therapeutic opportunity for HBV patients with cancer.